MANTLE PB PARADOXES: THE SULFIDE SOLUTION - Hart S.R.; Gaetani G.A. (My University, 2006)
There is growing evidence that the budget of Pb in mantle peridotites is largely contained in sulfide, and that Pb partitions strongly into sulfide relative to silicate melt. In addition, there is evidence to suggest that diffusion rates of Pb in sulfide (solid or melt) are very fast. Given the possibility that sulfide melt “wets” sub-solidus mantle silicates, and has very low viscosity, the implications for Pb behavior during mantle melting are profound. There is only sparse experimental data relating to Pb partitioning between sulfide and silicate, and no data on Pb diffusion rates in sulfides. A full understanding of Pb behavior in sulfide may hold the key to several long-standing and important Pb paradoxes and enigmas. The classical Pb isotope paradox arises from the fact that all known mantle reservoirs lie to the right of the Geochron, with no consensus as to the identity of the “balancing” reservoir. We propose that long-term segregation of sulfide (containing Pb) to the core may resolve this paradox. Another Pb paradox arises from the fact that the Ce/Pb ratio of both OIB and MORB is greater than bulk earth, and constant at a value of 25. The constancy of this “canonical ratio” implies similar partition coefficients for Ce and Pb during magmatic processes (Hofmann et al. in Earth Planet Sci Lett 79:33–45, 1986), whereas most experimental studies show that Pb is more incompatible in silicates than Ce. Retention of Pb in residual mantle sulfide during melting has the potential to bring the bulk partitioning of Ce into equality with Pb if the sulfide melt/silicate melt partition coefficient for Pb has a value of ~ 14. Modeling shows that the Ce/Pb (or Nd/Pb) of such melts will still accurately reflect that of the source, thus enforcing the paradox that OIB and MORB mantles have markedly higher Ce/Pb (and Nd/Pb) than the bulk silicate earth. This implies large deficiencies of Pb in the mantle sources for these basalts. Sulfide may play other important roles during magmagenesis: (1) advective/diffusive sulfide networks may form potent metasomatic agents (in both introducing and obliterating Pb isotopic heterogeneities in the mantle); (2) silicate melt networks may easily exchange Pb with ambient mantle sulfides (by diffusion or assimilation), thus “sampling” Pb in isotopically heterogeneous mantle domains differently from the silicate-controlled isotope tracer systems (Sr, Nd, Hf), with an apparent “de-coupling” of these systems.
Keywords: SULFIDE; OLIVINE; MANTLE PERIDOTITE; ISOCHRON; MANTLE RESERVOIR